Outposts. Design inventories for a possible future between biology and the artefact - Vincenzo Moschetti (Agathón)
The theme of the forest reconfigures new maps to explore. Numerous reports (FAO, ISTAT, UE) demonstrate an ‘advance’ of biological systems, building through heredity grey areas within which ‘nature’ is incessantly at work. It is not a question of deciphering a possible and renewed domestication of the ‘forests’, but rather of a preferable use of the devices – as revealed by Agamben – for identifying how architecture can place itself within a completely autonomous organism. The essay makes use of the examples offered by Giorgini’s Casa Esagono in Baratti and Perugini’s Casa Albero in Fregene, together with the more recent Horizontal Skyscraper by Herzog & de Meuron, to manifest a preferable advance, parallel to that of forests which, according to the evidence available, will continue to expand in the future and within which it is desirable, if not necessary, to ‘work’ using the figure of the outpost.